The fallacy of youth participation. A critical look at the speech of the youth participation in Colombia - Moreno-Huertas, Néstor (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Youth participation has been presented as one of the new contributions within the speech of institutional offer towards young people. Nevertheless, this speech does not recognize the universe which gives significance to this population, promoting a rupture between participation and social mobilization.This situation enables a distancing between population and institutions which intend to promote youth participation. The rupture has its roots on the lack of interest of these institutions for including in a real way youth population in the political agenda.